(untitled) (Tribhuvan University Journal of Microbiology, 2023)
Objectives: The study aims to compare the 16srRNA sequence of Bacillus thuringiensis var israelensis available in the National Center for Biotechnology Information, database, the sequence length, the relatedness, identity, and ancestral property by constructing a phylogenetic tree and by basic local alignment tool. Methods: The 16srRNA sequence of all the Bacillus thuringiensis var israelensis was retrieved from the database. A basic local alignment tool was used to study the description of the sequences, the percent identity, graphical summary, and alignment. Mega software was used to draw the phylogenetic tree. Results: The total number of mosquitocidal 16srRNA gene sequences was 19. One sequence VCRC-B17 strain was the complete genomic sequence deposited other 18 hits were partial sequences. The Expected value, percent identity, maximum, and total score of 18 hits shows a significant match with the query sequence VCRC-B17. The graphic summary result displays that the 18 hits align with the query sequence as they are coded with the highest score coding color bar, red with a ≥ 200 alignment score. The phylogenetic tree did not support the monophyletic status indicating there is a diversity in the strain. Conclusion: The 19 sequences deposited in the database are identified as a mosquito larvicidal Bacillus thuringiensis var israelensis based on the alignment score or match even though they do not possess an equal base pair length with the query sequence.